Pengaruh Kreativitas, Modal, Dan Kesetaraan Gender Terhadap Kinerja Pengusaha Wanita UKM Di Palembang - Supriani, Yun (Universitas Muhammadiyah Palembang, 2017)
ABSTRACTPurpose - This study is based on research by the author on 30 SMEs in Palembang.Design/methodology - The research was carried out within 6 months, where the study was carried out using SPSS 17. The SME women entrepreneurs studied were 18 women entrepreneurs who opened the business pempek, 8 entrepreneurs songket, and 4 entrepreneurs sumsel handicrafts.Findings – The results showed that Correlation Coefficient Kreeativitas variable (X1) of 0.488 means that if creativity to grow / increase the unit then Performance (Y) increased by 0,488 or 48.88% as well as the regression coefficient of variable capital. If the capital increase satuanmaka the capital variable (X3), an increase of 0.341, and if the variable Gender Equality (X3) experienced increase of 0,292.sehingga can improve SMEs in Palembang Women Kinerjapengusaha by 29.2%. The correlation value (R) of 0.921 means creativity, capital and gender equality possessed a strong, positive relationship. .koefisien determination (R2) equal to 0, 519 = 59.1%. While the remaining 42.1% can be explained by other variables